2001
DOI: 10.1182/blood.v97.7.1975
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between α4β1/α5β1 and c-Kit results in opposing effect on growth and survival of hematopoietic cells via the activation of focal adhesion kinase, mitogen-activated protein kinase, and Akt signaling pathways

Abstract: IntroductionAdhesive interactions between hematopoietic progenitor and stem cells and the hematopoietic microenvironment play a critical role in maintaining hematopoiesis. [1][2][3][4][5] Hematopoietic growth factors are potent regulators of hematopoiesis. In addition, these proteins have been implicated in modulating adhesion between hematopoietic progenitor cells and extracellular matrix proteins via changes in integrin receptor activation. [6][7][8][9] The role of adhesion molecules alone or with growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 70 publications
5
75
3
Order By: Relevance
“…Differentiation towards the nonlymphoid lineages suggests that cytokine combinations that induce erythroid differentiation (and contain Epo) also induce a strong upregulation of CD111 expression on the cell surface. This is compatible with the high numbers of CFU-E that were detected while culturing CD34 + /CD111 bright cells in methyl-cellulose assays, and with the increased expression of CD49d and CD49e on CD34 + /CD111 bright cells, 49 as well as with the increased expression of CD11a on CD34 + /CD111 dim cells. 50 The kinetics of CD111 expression, compared with the kinetics of expression for other useful markers of the erythroid lineage (CD71, CD36 and glycophorin A) suggests that CD111 may be highly upregulated during the transition from the BFU-E stage, to the CFU-E stage; 50,51 during erythroid differentiation in vitro, CD111 expression appears to peak after approximately 1 week of culture, to decrease later.…”
Section: Discussionsupporting
confidence: 61%
“…Differentiation towards the nonlymphoid lineages suggests that cytokine combinations that induce erythroid differentiation (and contain Epo) also induce a strong upregulation of CD111 expression on the cell surface. This is compatible with the high numbers of CFU-E that were detected while culturing CD34 + /CD111 bright cells in methyl-cellulose assays, and with the increased expression of CD49d and CD49e on CD34 + /CD111 bright cells, 49 as well as with the increased expression of CD11a on CD34 + /CD111 dim cells. 50 The kinetics of CD111 expression, compared with the kinetics of expression for other useful markers of the erythroid lineage (CD71, CD36 and glycophorin A) suggests that CD111 may be highly upregulated during the transition from the BFU-E stage, to the CFU-E stage; 50,51 during erythroid differentiation in vitro, CD111 expression appears to peak after approximately 1 week of culture, to decrease later.…”
Section: Discussionsupporting
confidence: 61%
“…Our observations nevertheless suggest that in vitro data do not necessarily reflect the situation in vivo. Indeed, c-kit may exert divergent functions depending on a modulation by milieu factors and differential interactions with intracellular effector pathways (Kapur et al, 2001), and alternative splicing of c-kit mRNA may elicit opposite effects (Caruana et al, 1999). Moreover, no comparative information concerning the biological behavior of neuroblasts with and without c-kit expression can be derived from these data (Cohen et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there have been also several reports demonstrating the negative effects of cell adhesion on cell survival. Integrinmediated adhesive interaction with FN was shown to cause apoptosis in myeloid cell lines (11,12) and erythroid progenitor cells (13). Although the molecular mechanisms underlying apoptosis were not defined, these studies clearly showed that integrin-mediated adhesion plays a negative role in the survival of hematopoietic progenitor/tumor cells.…”
mentioning
confidence: 90%